EVALUASI KUALITAS PERANGKAT LUNAK DENGAN ISO/IEC 25010:2011 (STUDY KASUS : APLIKASI FIRST AID PADA PLATFORM ANDROID) - Muhamad Harun (Jurnal Akrab Juara, 2018)
The patterns and ways in which people work to access information have changed with smartphones. Thus encouraging the development of reliable quality information systems in order to assist and facilitate humans, especially in the field of health by creating a first aid application. The quality of software in value as things that affect the success of the software. So to be able to obtain good software quality needs to be evaluated software based on ISO/IEC 25010:2011 which is part of Systems and software Quality Requirements and Evaluation (SQuaRE) replace ISO/IEC 9126-1:2001 by categorizing product quality into characteristic which consists of Functional Suitability, Performance efficiency, Compatibility, Usability, Reliability, Security, Maintainability, Portability. So it can help developers to design high quality systems Keywords: android app, evaluation, ISO / IEC 25010: 2011, software quality.